HUBUNGAN RESISTIN SERUM DENGAN PROGRESIVITAS KETEBALAN TUNIKA INTIMAMEDIA KAROTIS PASCASTROKE ISKEMIK - Marcus Adityawan Bahroen,* Dodik Tugasworo,* Dwi Pudjonarko,* Retnaningsih* (Neurona Majalah Kedokteran Neuro Sains, 2016)
INTRODUCTION RESISTIN FACILITATES THE THICKENING OF BLOOD VESSEL ENDOTHELIUM AND ALSO INFLUENTIAL IN FAT METABOLISM THEREBY PROMOTING ATHEROSCLEROSIS CAROTID INTIMAMEDIA THICKNESS CIMT IS A WELLKNOWN SURROGATE MARKER FOR ATHEROSCLEROSIS NEVERTHELESS THE ROLE OF RESISTIN IN THE PROGRESSION OF ATHEROSCLEROSIS IN POSTISCHEMIC STROKE PATIENTS HAS NOT BEEN STUDIED